2019
DOI: 10.1080/21645515.2019.1565259
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of an intramuscular split-virion quadrivalent inactivated influenza vaccine in individuals aged ≥ 6 months in India

Abstract: A quadrivalent split-virion inactivated influenza vaccine (IIV4; Fluzone® Quadrivalent, Sanofi Pasteur) has been available in the US since 2013 for individuals aged ≥ 6 months. Here, we describe the results of an open-label, multicenter trial (WHO Universal Trial Number U1111-1143-8370) evaluating the immunogenicity and safety of IIV4 in Indian children aged 6-35 months and 3-8 years, adolescents aged 9-17 years, and adults aged ≥ 18 years (n = 100 per group). Post-vaccination hemagglutination inhibition titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The symptoms and incidence rates of adverse reactions in all recipients that occurred in this study are consistent with the results of previous studies in which the common adverse reaction found was pressure or pain at the injection site [ 9 ]. Influenza is an acute respiratory infectious disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The symptoms and incidence rates of adverse reactions in all recipients that occurred in this study are consistent with the results of previous studies in which the common adverse reaction found was pressure or pain at the injection site [ 9 ]. Influenza is an acute respiratory infectious disease.…”
Section: Discussionsupporting
confidence: 91%
“…Adopting an immunization schedule based on the most recent scientific research for specific groups of individuals will help to ensure total protection. It has been shown that vaccinating children against influenza virus can increase their resistance [ 9 ]. However, the optimal vaccination regimen has not yet been precisely defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms are temporary and usually subside within two to six days. Serious adverse events from influenza vaccines, such as severe allergic reactions, are extremely rare [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although intramuscular administration of a polyvalent formulation of chemically inactivated or disrupted influenza virus is the most common type of vaccine for seasonal influenza both in adults and children (25), intranasal administration of a live attenuated influenza virus (LAIV) in the respiratory tract is also utilized as a method of vaccination (26). However, this formulation is restricted to children more than 2 years of age and adults (27,28) because of reports of increased risk of reactive airway disease (29,30) and increased concern over the presence of underlying asthma in young vaccine recipients (31,32).…”
Section: Introductionmentioning
confidence: 99%